Stress and Work Performance Among Public Servants in Ghana - Ishmael Adams; Solomon Tetteh (Universitas Sultan Ageng Tirtayasa, 2022)
The health literature has often emphasized the negative impact of stress on work performance among health workers. However, the impact of stress and its key predictors on work performance among public sector staff in developing countries remains unknown. This study has examined the influence of stress and its main predictors on work performance among public servants in an African country. Using Ghana’s public sector as a case, 157 staff of the Office of the Head of Civil Service (OHCS) and its aligned institutions responded to a self-administered survey. Results indicate that matching income to expenses was the most significant predictor of stress. Also, while stress generally negatively impacted work performance, a minimum level of stress was found to have a positive impact on work performance. The findings reinforce the importance of improved remuneration for reducing work stress towards improved work performance among public sector departments in developing countries.